Wearable Fall Detection Device - Zahazunizam, Muhammad Mu'az Aiman; Mashori, Sumaiya (Progress in Engineering Application and Technology, 2022)
A family member’s constant monitoring of the well-being and health of the elderly, particularly those who live alone, is required. This is due to the significant risk of death from falls among the elderly, particularly those who live alone and sick. On the other hand, constant monitoring of the elderly takes time and disrupts the work-life balance of their family members. Wearable Fall Detection Device (WFDD) had been developed to be wear at the wrist like a smart watch and the family members could monitor their elderly movement by using smart phone. WFDD allow caregivers and family members to be notified when an older person’s wearable gadget detects a fall. This approach is supposed to make it easier for family members to keep an eye on their senior relatives. Using WFDD, a caregiver can provide equal and constant attention to numerous elderly people at the same time. Meanwhile, due to the elderly will not feel controlled while being observed, this wearable device will not cause any discomfort to them. As a result, WFDD could help the family members to monitor their loves one and notify an alert if falls happen. Hence, the family member able to call an emergency service for help as soon as the fall happen and suppose able to lower the probability of elderly dying due to falls.